2004
DOI: 10.1152/ajplung.00288.2003
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated transfer of the 1-cys peroxiredoxin gene to mouse lung protects against hyperoxic injury

Abstract: 1-Cys peroxiredoxin (1-cysPrx) is a novel antioxidant enzyme that has been shown to reduce a broad spectrum of peroxides including phospholipid hydroperoxides. We tested the hypothesis that adenovirus-mediated transfer of the 1-cysPrx gene can protect lungs of mice from oxidant injury. Mice infected with AdLacZ/AdNull were used as a control (AdCon). X-galactosidase staining revealed widespread expression of the LacZ gene in airways and lung alveoli. Compared with AdCon, 1-cysPrx expression was increased about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 23 publications
4
45
0
Order By: Relevance
“…These findings suggested that forced expression of Prdx6 in endangered tissues and organs could protect cells from ROSmediated cell damage, a hypothesis that is supported by the observation that adenoviral overexpression of Prdx6 in the lung protected mice from hyperoxic injury. 13 ROS detoxification is of particular importance in the epidermis, which is frequently exposed to ROS-generating xenobiotics and UV irradiation, resulting in accumulation of oxidative damage. A role of Prdx6 in the antioxidative defense of keratinocytes was suggested by our previous studies, which demonstrated a strong overexpression of Prdx6 in keratinocytes of wounded and psoriatic skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggested that forced expression of Prdx6 in endangered tissues and organs could protect cells from ROSmediated cell damage, a hypothesis that is supported by the observation that adenoviral overexpression of Prdx6 in the lung protected mice from hyperoxic injury. 13 ROS detoxification is of particular importance in the epidermis, which is frequently exposed to ROS-generating xenobiotics and UV irradiation, resulting in accumulation of oxidative damage. A role of Prdx6 in the antioxidative defense of keratinocytes was suggested by our previous studies, which demonstrated a strong overexpression of Prdx6 in keratinocytes of wounded and psoriatic skin.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, Prdx6 has been reported to have phospholipase A 2 activity. 10,11 Previous studies have shown that overexpression of Prdx6 in different cell types protects from ROS-induced cytotoxicity, [12][13][14] whereas knockdown of this enzyme 15 or ablation of the gene in mice resulted in enhanced sensitivity to oxidative injury. 16 -18 However, the role of Prdx6 in the skin is as yet unknown.…”
mentioning
confidence: 99%
“…113,114 Since each of the two enzymatic functions of Prx6 can operate in the absence of the other, 111 it has been possible to demonstrate, by mutational knockouts, that the peroxidatic, but not the lipolytic, function is required for cell survival under cytotoxic oxidative stress. 115 The peroxireductase activity of Prx6 is severalfold higher than the phospholipase activity, 109 and likely to predominate under the slightly alkaline conditions prevailing in the cytosol.…”
Section: Autophagosomal Membrane Proteinsmentioning
confidence: 99%
“…These activities require the binding of Prdx6 to phospholipids in a specifi c orientation in relation to cys47, the active site for GPx activity, and to S32-H26-D140, the catalytic triad for PLA 2 activity ( 2, 3 ). The GPx activity of Prdx6 plays a key role in the antioxidant defense of the lung, as well as other organs (4)(5)(6)(7)(8), and has been shown recently to participate in the repair of peroxidized cell membranes by reduction of phospholipid hydroperoxides ( 3,9 ). The PLA 2 activity of Prdx6 also participates in the repair of peroxidized cell membranes by liberating the sn -2 oxidized fatty acid to generate lysophosphatidylcholine (LPC) ( 9,10 ).…”
mentioning
confidence: 99%